Multi-objective aerodynamic and structural optimization of a wind turbine blade using a novel adaptive game method. Issue 8 (2nd August 2020) - Meng, Rui; Wang, Lu; Cai, Xin; Xie, Neng-gang
ABSTRACT: In this study, an integrated structural and aerodynamic optimization of a wind turbine blade is performed. A parameterized finite element model of a blade is first presented based on its aerodynamic shape and structural design. Next, a multi-objective optimization model with 27 design variables and complex constraints is established based on annual energy production and blade mass. A novel adaptive win–stay, lose–shift (WSLS) game method is proposed to obtain an integrated optimal solution. In this method, aerodynamic and structural targets are regarded as two game players with profit interaction and conflict. Notable features of this method include adaptive adjustment of a game player's strategy space and behavioural switching between competitive and cooperative modes according to game rules. An engineering blade example is presented and all goals show improvements over the initial solutions. A comparison and analysis of the results demonstrate proof of the principles of this method.